Prevalence of Laryngopharyngeal Reflux in Patients with Gastroesophageal Reflux Disease Undergoing Upper Esophagogastroduodenoscopy - Regmi Chalise, Sangita; Khadka, Subash; Mukhia, Rupesh; Thapa, Abishek; Gautam, Santosh; Sah, Mukesh; Ranjan, Rashmi (Journal of Institute of Medicine Nepal, 2019)
Introduction Gastroesophageal reflux disease (GERD) has been defined as the retrograde flow of gastric contents into the esophagus. Laryngopharyngeal reflux (LPR) is one of the manifestations of GERD which can be diagnosed clinically by Reflux Symptom Index (RSI) and Reflux Finding Score (RFS). The aim of this study was to find the prevalence of laryngopharyngeal reflux in patients with GERD undergoing upper esophagogastroduodenoscopy. Methods This was a prospective cross sectional study and all the patients visiting author’s institute with GERD undergoing upper esophagogastroduodenoscopy were included. All the relevant data on history, examination, RSI scores, RFS scores and upper esophagogastroduodenoscopy findings were recorded in the standard proforma and data were analysed. Results A total of 205 patients with GERD and undergoing upper esophagogastroduodenoscopy were included whose mean age was 46.1 years. The female to male ratio was 1.3:1. The most common presenting symptoms in our study was hoarseness (97%) followed by coughing (90.7%). The mean RSI score was 11.6. The symptom prevalence of LPR was 23.4%. The prevalence in between age groups and gender was not significantly different. The mean RFS score was 9.5. The prevalence of LPR by RFS assessment was 64.4%, which is significantly more than the prevalence assessed by RSI (23.4%). Conclusion The prevalence of LPR in patients with GERD by RSI was less than the prevalence by RFS. So both the tools need to be used simultaneously to make the diagnosis and not recommendable to use independently.